The combination of irradiation biofertilizer of rhizosphere microbes consortium inoculant (IMR) and inorganic fertilizer on the growth of kale in a floating raft hydroponic system. Issue 1 (November 2021) - Dewi, A K; Rahayu, S; Dwimahyani, I; Khairunnisa, N; Suryadi, E
Abstract: A hydroponic floating system is a working system where a plant is placed in a floating net pot on the surface of water. In hydroponic systems, the content of inorganic fertilizers contained in the media is the main source of nutrients for plants. The use of biological fertilizers is expected to reduce the dose of inorganic fertilizers applied to hydroponic systems. The main objective of this study was to obtain a combination of inorganic fertilizers with Inoculant of Rhizosphere Microbial Consortium (IMR) and biofertilizer which has the most influence on the N content, growth and production of kale plant. There are five different treatments on hydroponic floating system viz 100% inorganic fertilizer (control), 100% inorganic fertilizer + IMR (Pa), 75% inorganic fertilizer + IMR (Pb), 50% inorganic fertilizer + IMR (Pc), and 25% + IMR (Pd), where 100% inorganic fertilizer is equivalent to 10 mL / L and the amount of IMR given to each treatment was 10 ml/L. The method used in this research was descriptive comparative method, using primary data which is then analysed quantitatively such as using graphs, and T-test. The results of the research showed that giving a combination of 100% biological fertilizer and 50% inorganic fertilizer, can reduce the use of inorganic fertilizers by 50%, and gave the best and significant influence on plant height 34.41 cm, leaves as much as 30 strands, root length 24.27 cm, and the harvest weight 80.97 grams. The combination of 100% biological fertilizer and 50% inorganic fertilizer does not give a combination of N content of the kale plant.